Association between biventricular pacing and incidence of ventricular arrhythmias in the early post‐operative period after left ventricular assist device implantation. (19th March 2022) - Chou, Andrew; Larson, John; Deshmukh, Amrish; Cascino, Thomas M.; Ghannam, Michael; Latchamsetty, Rakesh; Jongnarangsin, Krit; Oral, Hakan; Morady, Fred; Bogun, Frank; Aaronson, Keith D.; Pagani, Francis D.; et al.
Abstract: Introduction: Cardiac resynchronization therapy (CRT) and left ventricular assist devices (LVAD) improve outcomes in heart failure patients. Early ventricular arrhythmias (VA) are common after LVAD and are associated with increased mortality. The association between left ventricular pacing (LVP) with CRT and VAs in the early post‐LVAD period remains unclear. Methods: This was a retrospective study of all patients undergoing LVAD implantation from 1/2016 to 12/2019. Patients were divided into those with CRT and active LVP (CRT‐LVP) immediately post‐LVAD implant versus those without CRT‐LVP. Implantable cardiac defibrillator electrograms were reviewed and early VAs were defined as sustained ventricular tachycardia (VT)/ventricular fibrillation occurring within 30 days of LVAD implantation. Results: Of 186 included patients (mean age 53 years, 75% male, mean body mass index 28), 72 had CRT devices, 63 of whom had LV pacing enabled after LVAD implant (CRT‐LVP group). Patients with CRT‐LVP were more likely to have VA in the early postoperative period (21% vs. 4%; p = .0001). All 9 patients with CRT in whom LVP was disabled had no early VA. Among those with early VA, patients with CRT‐LVP were more likely to have monomorphic VT (77% vs. 40%; p = .07). In multiple logistic regression, CRT‐LVP pacing remained an independent predictor of early VA after adjustment for history of VA and AF. Conclusions: Patients with CRT‐LVP after LVAD implant had a higher incidence of early VA (specifically monomorphic VT). Epicardial LV pacing may be proarrhythmic in the early postoperative period after LVAD.